The Association between Isolated Oligohydramnios at Term and Pregnancy Outcomes - حسن, لؤي (Latakia University Journal -Medical Sciences Series, 2021)
Background: Conflicting data exist concerning the implications of isolated oligohydramnios on pregnancy outcome at term. Aim: To assess the association between isolated oligohydramnios at term and pregnancy outcome in low-risk pregnancies. Materials and Methods: This was a retrospective cohort study of term pregnancies with sonographic finding of isolated Oligohydramnios (amniotic fluid index (AFI) <5 cm) between 2017 and 2019, conducted at Obstetrics and Gynecology Department, Tishreen University Hospital, Lattakia, Syria, during the period between January 2019 – January 2020. Outcome was compared to a control group of pregnancies with normal AFI (5–25 cm). Pregnancies complicated by hypertension, diabetes, deviant fetal growth or chromosomal/ structural abnormalities were excluded. Composite adverse outcome included cesarean section delivery, low Apgar score, neonatal intensive care admission, meconium aspiration syndrome, or intubation. Results: Overall, 190 pregnancies complicated by isolated oligohydramnios were compared to 200 low-risk pregnancies with normal AFI. Isolated oligohydramnios was associated with a higher rate of induction of labor (29.8 % vs. 4 %, p < 0.05), cesarean section delivery (21.6 vs. 13 %, p < 0.05) and composite adverse outcome (13.2 % vs. 7 %, p < 0.05). However, after adjusting for potential confounders as induction of labor and nulliparity using multivariable logistic regression analysis, isolated oligohydramnios was not found to be independently associated with increased risk for composite adverse outcome (OR 1.07, 95 % CI 0.9–1.31, p = 0.87). Conclusion: Isolated oligohydramnios at term by itself is not associated with increased obstetrical morbidity.